CBT-I Online Efektif Meningkatkan Kualitas Tidur Lansia - Faridah, Ida; Rekawati, Etty; Sahar, Junaiti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the effectiveness of implementing online CBT-I on older adults with sleep disorders. The method used is a Systematic Review guiding a search of 4 databases, ScienceDirect, Scopus, PubMed, and UI Lib, in October 2023 with article publication years starting from 2019-2023 to identify all relevant journal articles. The search technique follows the PRISMA flow. The research results showed that online CBT-I was proven to be effective in treating insomnia sleep disorders in the elderly. CBT-I can even treat secondary disorders due to insomnia, such as depression and anxiety. In conclusion, Online CBT-I can be implemented in health services provided that there is adequate computer and internet accessibility. Keywords: Online CBT, Insomnia, Sleep Disorders, Elderly